PENDAMPINGAN MASYARAKAT DALAM PENERAPAN SISTEM PENGELOLAAN SAMPAH MENUJU DESA MAPPESANGKA YANG BERSIH DAN MANDIRI ENERGI - Firdaus; Dessy Ana Laila Sari; Mudarris; Hasrul Bakri; Hilda Ashari (Journal of Engineering Service and Innovation, 2026)
Waste management in rural areas remains a serious challenge affecting environmental health and community quality of life. This community service program was conducted in Mappesangka Village with the aim of assisting the community in implementing an appropriate technology-based waste management system while promoting a clean and energy-independent village. Implementation methods included field observation, public counselling, participatory training, and the construction of a communal waste incinerator. The program actively involved the implementation team, village officials, and local communities. Results indicate a significant improvement in community understanding of proper waste management practices, the availability of a communal incinerator capable of reducing waste volume by 70–80%, and the formation of collective awareness toward a clean and energy-independent village. The constructed incinerator also has the potential to be developed as an alternative energy source through integration of thermoelectric modules. This program is expected to serve as a replicable assistance model for other surrounding villages.